Effects of synthesis and processing on supersaturated rare earth-doped nanometric SnO2 powders - Weber, I. T.; Maciel, A. P.; Lisboa Filho, Paulo Noronha [UNESP]; Longo, Elson [UNESP]; Leite, E. R.; Paiva-Santos, C. O.; Maniette, Y.; Schreiner, W. H. (Amer Chemical Soc, 2002)
This paper presents and discusses some of the results of the effects of processing on rare earth-doped nanosize SnO2. Several relevant factors that may influence the characteristics of the final product are studied. The influence of two preparation routes and two heat-treatment conditions on the incorporation of dopants is investigated. The route whereby a soluble salt is used as the dopant source is found to provide the highest degree of dopant incorporation, even under the least favorable heat-treatment conditions.